Quantum gravity and cosmology based on conformal field theory - Hamada, Kenji, 1962- (Cambridge Scholars Publishing, 2018)
Of Gravitational CountertermsQED in Curved Space; Normal Products; Restrictions from Correlation Functions; Determination of Gravitational Counterterms; Determination of Conformal Anomalies; Casimir Energy; Chapter Ten; D-Dimensional Action and Renormalization Procedure; Kinetic Terms and Interactions; Gauge-Fixing; Calculations of Renormalization Factors; Background-Metric Independence Revisited; Diffeomorphism Invariant Effective Actions; Renormalization of Mass Parameters; Physical Cosmological Constant; Chapter Eleven; Instability and Evolution of Fluctuations; Friedmann Universe